Batas Batas Penerapan Asas Kebebasan Berkontrak dalam Perjanjian Baku melalui Media Elektronik Antarpelaku Usaha di Era Digital - Retaly, Andrea Tamaranova; Kansil, Christine S.T. (AL-SULTHANIYAH, 2025)
This study analyzes the boundaries of the principle of freedom of contract in standard form agreements conducted through electronic media between business actors (B2B) in the digital era. Digital transformation promotes transactional efficiency but also generates legal imbalances as contract clauses are often unilaterally determined by the dominant party. Using a normative juridical and conceptual approach, this study places the Indonesian Civil Code (KUHPerdata) as the primary analytical framework, complemented by ITE Law, Trade Law, and PP PSTE. The findings reveal that freedom of contract in digital transactions is not absolute but limited by principles of fairness, propriety, and legal accountability. Specific regulations under PP PSTE and ITE Law establish administrative and technical constraints on electronic contracting, while the Civil Code remains the normative foundation ensuring balance and legal protection among business actors in the digital age.